2020
DOI: 10.34197/ats-scholar.2019-0024in
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in the Pulmonary and Critical Care Medicine Pipeline. Trends in Gender, Race, and Ethnicity among Applicants and Fellows

Abstract: Background : The diversity in pulmonary and critical care medicine (PCCM) training programs in the United States has not been systematically evaluated, despite emphasis on workforce diversity and its role in improving gender and racial healthcare disparities. Objectives : We analyzed the diversity of the PCCM pipeline by gender, race, and ethnicity over the last 10 years. Methods : The PCCM pipeline was defined as internal medicine residents, fellowshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…This includes the overall proportion of intensivists who are women and the proportion of women who are conference speakers, lead authors, and peer reviewers and in leadership positions within critical care societies ( 6 – 10 ). A recent analysis revealed that fewer than one-third of fellows in US critical care training programs are women and that the proportion of women trainees appears to have plateaued over the last decade ( 11 ), In a 2019 Canadian qualitative study examining the drivers of gender inequity in critical care medicine, respondents highlighted the inflexible and long work hours, the lack of women role models, and the overt value placed on traditionally masculine traits ( 12 ). The latter factor may also have an impact on trainee evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the overall proportion of intensivists who are women and the proportion of women who are conference speakers, lead authors, and peer reviewers and in leadership positions within critical care societies ( 6 – 10 ). A recent analysis revealed that fewer than one-third of fellows in US critical care training programs are women and that the proportion of women trainees appears to have plateaued over the last decade ( 11 ), In a 2019 Canadian qualitative study examining the drivers of gender inequity in critical care medicine, respondents highlighted the inflexible and long work hours, the lack of women role models, and the overt value placed on traditionally masculine traits ( 12 ). The latter factor may also have an impact on trainee evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Taking a closer look at equity in recruitment requires us to examine the ways in which UIM candidates, and particularly Black persons, experience structural discrimination. In the pipeline for PCCM, there is a marked loss in the percentage of Black Internal Medicine (IM) residents applying to PCCM fellowships and subsequently matching ( 8 ). Below, we discuss how bias in United States Medical Licensing Exam (USMLE) scores, letters of recommendation (LORs), and undergraduate medical education clerkship narrative evaluations can manifest and impact selection processes and propose potential methods to mitigate that bias.…”
Section: Definitionsmentioning
confidence: 99%
“…Finally, issues surrounding gender equity and diversity in medicine are critical to our practice and the education and training of our next generation. We have published important work in this area, such as an article by Santhosh and Babik ( 10 ) that reports trends in gender, race, and ethnicity among pulmonary/critical care medicine fellows and applicants over the last decade and finds continued disparities. Recognizing the need to openly address the role structural racism plays in persistent disparities in medicine, ATS Scholar has sought to publish papers that provide meaningful insight and propose thoughtful solutions to this issue in health profession education.…”
mentioning
confidence: 99%